PENGARUH IMPLEMENTASI KEBIJAKAN PEMERINTAH KABUPATEN ROKAN HULU TERHADAP PERCEPATAN PENGHAPUSAN KEMISKINAN EKSTREM DI DESA RAMBAH HILIR TENGAH KECAMATAN RAMBAH HILIR - Hasbi, Hasbi (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2025)
In an effort to eradicate extreme poverty, the Government of Rokan Hulu Regency took steps to implement the first policy strategy, reducing the expenditure burden. Second, increase in income. Third, the reduction in the number of pockets. The aims of this study were (1) to find out what the Rokan Hulu Regency Government's Policies/Programs for Accelerating the Elimination of Extreme Poverty in Rambah Hilir Tengah Village, Rambah Hilir District. (2) Knowing the Effect of Policy Implementation of the Rokan Hulu District Government on the Acceleration of the Elimination of Extreme Poverty in Rambah Hilir Tengah Village, Rambah Hilir District. The research uses a quantitative approach with a descriptive type, the population is Extremely Poor Families based on Data Targeting the Acceleration of Extreme Poverty Reduction (P3KE), consisting of deciles 1-6 with a sample of 332 households. All instruments have been tested so that they meet the validity test requrements using product correlation and reliability using Cronbach's alpha. Data analysis used the T-test and the large percentage of influence used the Adjuster R Square coefficient of determination. The results of the study show that (1) a reduction in expenditure burden (X1) has no effect on extreme poverty (Y) with a Sig (Perial) value of X1 to Y of 0.143 > 0.05 and a tcount value of 1.470 < ttable 1.967. (2) Increased Income (X2) has a significant effect on Extreme Poverty (Y). (3) minimizing the poverty enclave (X3) has a significant effect on Extreme Poverty (Y), with a Sig (Perial) value of X3 to Y of 0.00 < 0.05 and a tcount value of 42.448 > ttable 1.967. Reducing Expenditures, Increasing Incomes and Minimizing Poverty Pocket Areas Do Contribute to Extreme Poverty.